2014
DOI: 10.3109/13816810.2014.973045
|View full text |Cite
|
Sign up to set email alerts
|

Classification and Management of Seeds in RetinoblastomaEllsworth Lecture Ghent August 24th 2013

Abstract: Retinoblastoma has the unique capacity to accelerate its own intra-ocular propagation by adopting semi-solid or even liquid growth properties through seeding. Until recently, the presence of any degree of seeding was mostly incompatible with successful conservative management, due to the multiresistant nature of the seeds. Surprisingly, this well-recognized retinoblastoma behavior has not undergone any detailed description of seeding patterns and anatomic sites. In this paper, we describe the phenotypic variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
147
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(161 citation statements)
references
References 28 publications
(31 reference statements)
0
147
1
3
Order By: Relevance
“…After this treatment, at 6 months of age, she was noted to have persistently active vitreous seeding in the right eye and seeding from a recurrence in the left eye. It was decided to proceed with intravitreal melphalan injection in both eyes following the standard technique previously described by Munier [4]: a paracentesis is performed, withdrawing 0.1 ml of aqueous humor; an injection is done 3.25-3.5 mm from the limbus with a 32-gauge, 12-mm (0.5-inch) needle in a quadrant of the eye free of tumor; the needle is visualized behind the lens in the mid-anterior vitreous, and cryotherapy is applied as the needle is withdrawn from the eye; the eye is then shaken to distribute the chemotherapy, and the surface bathed in sterile water. The patient tolerated the first cycle of bilateral intravitreal melphalan injections with 30 μg for the right eye and 25 μg for the left eye without complication.…”
Section: Case Seriesmentioning
confidence: 99%
See 2 more Smart Citations
“…After this treatment, at 6 months of age, she was noted to have persistently active vitreous seeding in the right eye and seeding from a recurrence in the left eye. It was decided to proceed with intravitreal melphalan injection in both eyes following the standard technique previously described by Munier [4]: a paracentesis is performed, withdrawing 0.1 ml of aqueous humor; an injection is done 3.25-3.5 mm from the limbus with a 32-gauge, 12-mm (0.5-inch) needle in a quadrant of the eye free of tumor; the needle is visualized behind the lens in the mid-anterior vitreous, and cryotherapy is applied as the needle is withdrawn from the eye; the eye is then shaken to distribute the chemotherapy, and the surface bathed in sterile water. The patient tolerated the first cycle of bilateral intravitreal melphalan injections with 30 μg for the right eye and 25 μg for the left eye without complication.…”
Section: Case Seriesmentioning
confidence: 99%
“…Munier [4] described varying degrees of salt-and-pepper retinopathy, which occurs at the site of injection. The clinical grading system ranges from localized salt-and-pepper retinopathy at the anterior injection site (grade I) to diffuse chorioretinal toxicity with optic atrophy (grade V) [4]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 In 2014, Munier further described the phenotypic variability of retinoblastoma seeds and classified them into 3 subtypes, namely dust, spheres and clouds. 25 The vitreous seed classification can be predictive in regard to time to regression and number of intravitreal melphalan injections required: median time to regression was 0.6, 1.7, and 7.7 months for dust, spheres, and clouds, respectively, and median number of injections required to reach regression was 3, 5, and 8 injections, respectively. 26 In terms of tumour spread, Smith and Smith performed a systematic review in which they included 14 studies and more than 1,300 intravitreal injections, and concluded it is a rare occurrence.…”
Section: Novel Treatments For Intraocular Retinoblastomamentioning
confidence: 99%
“…23 In transgenic models tumors arise from the retina, whereas in orthotopic xenograft models tumor growth can be retinal and/or intravitreal, depending on the injection site (subretinal or intravitreal injection of tumor cells). We observed that tumor growth is more frequent in the vitreous, even if the injection was subretinal, due to the reflux of tumor cells into the vitreous cavity.…”
Section: Intraocular Retinoblastoma Mouse Modelsmentioning
confidence: 99%